Supporting Designers in Creating Cognition-centered Personalized Cultural Heritage Activities - Raptis, George E.; Avouris, Nikolaos M. (Adjunct Publication of the 27th Conference on User Modeling, Adaptation and Personalization - UMAP'19 Adjunct, 2019)
The heterogeneity of the audience of cultural heritage (CH) institutions introduces numerous challenges to the delivery of meaningful CH content. People with diverse cognitive characteristics are engaged with varying CH activities (e.g., games, guided visits) and considering that cognitive characteristics define the way we process information, our experience, behavior, and knowledge acquisition are influenced. Our recent studies provide evidence that human cognition should be considered as an important personalization factor within CH contexts, and thus, we developed a framework that delivers cognition-centered personalized CH activities. The efficiency and the efficacy of the framework have been successfully assessed, but, non-technical users may face difficulties when attempting to use it and create personalized CH activities. In this paper, we present DeCACHe which supports CH designers in developing cognition-centered personalized CH activities throughout different aspects of the design lifecycle. We also report a case study with one CH designer, who used our tool to produce two versions of his CH game for people with different cognitive characteristics.